H2020-MSCA-RISE-2016 - (:unkn) unknown (My University, 2026)
August 2016-present: €1.42 m successful grant application: ‘RESET-REliability and Safety Engineering and Technology for large maritime engineering systems’ in the program H2020-MSCA-RISE-2016 with partners from: LJMU (Coordinator/PI Professor Jin Wang in Marine Technology/€300 k budget), Aalto University, Instituto Superior Tecnico, Leibniz University, University of Plymouth, Mahidol University, Universiti Kebangsaan Malaysia, Universiti Teknologi Malaysia and Wuhan University of Technology (Status: in operation, Duration: 48 months). Extended participation in the preparation phase of the proposal; participation in all WPs.